The Role of Garcinia Mangostana Pericarp Extract as Antioxidant to Inhibit Atherosclerosis Process in High Risk Framingham Score Patient; Original Article - Aris Munandar ZI; Djanggan Sargowo; Ardian Rizal; Cholid Tri Tjahjono; Sasmojo Widito; Anna Fuji Rahimah (Heart Science Journal, 2021)
Atherosclerosis is the pivotal role of cardiovascular disease (CVD) involving oxidative stress dan inflammation. Garcinia has anti-oxidant property for years. This study was performed to explore the role of α-Mangostin of Garcia Mangostana Pericarp Extract as an antioxidant in inhibiting atherosclerotic process in patients with high-risk Framingham score. Methods: This prospective cohort design was led in 90 grown-ups with high hazard cardiovascular score which were resolved dependent on Framingham criteria, age 50–70 years of age. The patients were divided into two groups. One group was administered  2520 mg/day Garcinia mangostana Linn extracts (GMLE) in 3 divided doses for 90 days and the other group was administered a placebo. Parameters were Nitric Oxide (NO), Superoxide Dismutase (SOD) and Malondialdehyde (MDA), measured at baseline and after 90 days of treatment. An Independent T-test was performed for normally distributed data and the Mann-Whitney test was performed for abnormally distributed data with a significance level of p≤0.05.Results: Among the 77 subjects, we found that the plasma, MDA, concentration was significantly decreased compared with placebo 0,29±0.5 vs -0.04±0.25, respectively p = 0.011). SOD level significantly decreased in GMLE patients compared with placebo patients (0,17±0.79 vs -0.27±0.67, respectively, p=0.010) and we found that there was slightly increased in nitric oxide (NO), but no significantly compared with placebo 4.34±10.01 and 2.35±7.39, respectively, p = 0.37).Conclusion: Garcinia mangostana pericarp extract has an antioxidant effect that significantly inhibit atherosclerosis process in high-risk Framingham score patients